Glucose deprivation activates a metabolic and signaling amplification loop leading to cell death - Nicholas A Graham; Martik Tahmasian; Bitika Kohli; Evangelia Komisopoulou; Maggie Zhu; Igor Vivanco; Michael A Teitell; Hong Wu; Antoni Ribas; Roger S Lo; Ingo K Mellinghoff; Paul S Mischel; et al. (Molecular Systems Biology)
Abstract The altered metabolism of cancer can render cells dependent on the availability of metabolic substrates for viability. Investigating the signaling mechanisms underlying cell death in cells dependent upon glucose for survival, we demonstrate that glucose withdrawal rapidly induces supra‐physiological levels of phospho‐tyrosine signaling, even in cells expressing constitutively active tyrosine kinases. Using unbiased mass spectrometry‐based phospho‐proteomics, we show that glucose withdrawal initiates a unique signature of phospho‐tyrosine activation that is associated with focal adhesions. Building upon this observation, we demonstrate that glucose withdrawal activates a positive feedback loop involving generation of reactive oxygen species (ROS) by NADPH oxidase and mitochondria, inhibition of protein tyrosine phosphatases by oxidation, and increased tyrosine kinase signaling. In cells dependent on glucose for survival, glucose withdrawal‐induced ROS generation and tyrosine kinase signaling synergize to amplify ROS levels, ultimately resulting in ROS‐mediated cell death. Taken together, these findings illustrate the systems‐level cross‐talk between metabolism and signaling in the maintenance of cancer cell homeostasis.